On the st-spreading resistance of networks - Lapus, Raymond R. (Animo Repository, 2010)
Let G = (V, E) be an undirected loopless graph with possible parallel edges and s, t ∈ V. Assume that s is labelled at initial time step and that every labelled vertex spreads its labelling to neighbouring vertices with probability p in one time step. In this paper, we deal with the special case of this spread process called st-spread resistance of G. We establish the connection between the st-spread resistance to the Kulkarni's exponential spreading model where each edge in G is an exponential random variate with intensity p.